2010
DOI: 10.2459/jcm.0b013e328337d6f5
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitroprusside infusion prevents hypothyroidism in patients undergoing coronary artery bypass grafting: a prospective randomized clinical trial

Abstract: In this study, administration of SNP during cardiopulmonary bypass is shown to regulate free T3 and TSH levels positively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Our study are also comparable with Bettendorf et al (19) who reported a low plasma concentration in TSH, T3, T4, whereas their RT3 plasma concentration increased in children with congenital heart disease undergoing cardiac surgery. This is also consistent with study of Aslan et al (20) who found that TSH followed a similar pattern in patients who underwent cardiac surgeries under CPB. Ho et al (21) in his study found a similar pattern of TSH in patients undergoing cardiopulmonary bypass.…”
Section: ⅳ Resultssupporting
confidence: 93%
“…Our study are also comparable with Bettendorf et al (19) who reported a low plasma concentration in TSH, T3, T4, whereas their RT3 plasma concentration increased in children with congenital heart disease undergoing cardiac surgery. This is also consistent with study of Aslan et al (20) who found that TSH followed a similar pattern in patients who underwent cardiac surgeries under CPB. Ho et al (21) in his study found a similar pattern of TSH in patients undergoing cardiopulmonary bypass.…”
Section: ⅳ Resultssupporting
confidence: 93%